Assessment of the Readiness, Beliefs, and Practices Regarding Menstruation Among Women in Saudi Arabia - Alenizy H; Aleyeidi N; Almutairi R; Khosyfan L; Bedaiwi R; Alowaidah L; Alrushud H; Alfadda K; Alshamekh LA; Al Anazi N; Alshammari S; Alzahrani A; et al. (Dove Medical Press, 2024)
Helalah Alenizy,1 Nouran Aleyeidi,2 Reema Almutairi,3 Leen Khosyfan,3 Raghad Bedaiwi,3 Leen Alowaidah,3 Hissah Alrushud,3 Khawla Alfadda,3 Lujain A Alshamekh,3 Najd Al Anazi,3 Shuruq Alshammari,3 Amal Alzahrani,3 Hanin Alomar3 1Obstetrics and Gynecology, Department of Obstetrics and Gynecology, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Community Medicine, Department of Family and Community Medicine, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 3College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Nouran Aleyeidi, Department of Family and Community Medicine, College of Medicine, Princess Nourah Bint Abdulrahman University, P.O. Box 84428, Riyadh, 11671, Saudi Arabia, Tel +966 504304577, Email naaleyeidi@pnu.edu.saBackground: Menstruation is a natural process that occurs monthly in women. Although menstruation is a fundamental aspect of women's lives, their readiness for and beliefs about menstruation vary. Moreover, their practices during menstruation can be influenced by various factors, including age, education level, mother's education, and field of specialty. This study aimed to explore menstruation-related readiness, beliefs, and practices among women who had experienced menstruation in Saudi Arabia. In addition, the study aimed to evaluate the factors affecting these women's readiness, beliefs, and practices regarding menstruation.Patients and Methods: This cross-sectional online questionnaire-based study included 3471 women of different ages who had experienced menstruation. The participants were selected using convenience sampling from all regions of Saudi Arabia. The questionnaire was distributed between late December 2022 and March 2023 and included questions on demographics and menstruation-related readiness, beliefs, and practices.Results: Of the 3471 participants, 1627 (46.8%) were well prepared for menstruation. In addition, most of the study participants (80.2%) had positive beliefs about menstruation. However, the participants' menstrual practices varied. Over half of the participants (63%) used painkillers and approximately half (54.4%) used herbal medicine during menstruation.Conclusion: This study found that less than half of the participants were ready for menarche. In contrast, most participants displayed positive beliefs concerning menstruation. In terms of practices, the women exhibited certain dietary restrictions during their menstrual period and predominantly favored herbal remedies for pain relief over conventional painkillers. Implementing awareness campaigns and incorporating school education on menstrual readiness and hygiene is needed.Keywords: women's health, gynecology, menarche, hygiene, herbal medicine, menstrual pain